Determination of occurrence of atmospheric blockings over the Caspian Sea region in winters of 1959–2022, and influence of them on the ice regime of the Northern Caspian Sea - A. V. Kholoptsev; Zh. K. Naurozbayeva (Лëд и снег, 2024)
The ice regime of the Caspian Sea has pronounced influence on the heat and moisture exchange of the reservoir with the atmosphere, the state of the ecosystem, as well as human marine activities, including shipping, fishing, construction of hydraulic structures, etc. Consequently, the development of existing ideas about the causes of changes in the characteristics of the ice regime of such water bodies is actual and socially significant problem of limnology, hydrometeorology, ecology, and navigation. This study was aimed at determination the frequency of occurrence of atmospheric blockings over the Caspian region with standings longer 5 days in winter period of 1959–2022, and investigation of influence of them on the ice regime in the Northern area of the Sea. The following information and data were used: changes in hourly mean values of atmospheric pressure at the sea level, geopotential of isobaric surfaces 850, 500 and 300 hPa, presented in the ERA5 reanalysis; and observational data on air temperature and ice cover from hydrometeorological stations located in the Caspian region of Kazakhstan and Russia. It has been established that in the winter during a long standing of atmospheric blockings the mean daily air temperatures noticeably drop. The values of all the studied characteristics of every atmospheric blocking which occurred in 1959–2022 were estimated as well the influence of them on the ice regime in the North of the Caspian Sea was analyzed. The relationship between a decrease in the frequency of atmospheric blockings (AB), sums of negative air temperatures on its coasts, and the ice cover thickness in the corresponding areas of coastal waters has been revealed in the region. The longer the total AB duration, the lower is the air temperature, and the ice thickness in February is larger.